Characterization and potential antimicrobial effect of novel chitooligosaccharides against pathogenic microorganisms - Sanaa T. El-Sayed, Amal M. Ali, El-Sayed M. El-Sayed, Wafaa G. Shousha, Nagwa I. Omar (Journal of Applied Pharmaceutical Science, 2017)
Chitosan has antimicrobial activities against a wide range of food-borne microorganisms. It was poorly soluble in neutral solution, which makes them difficult to use in food and biomedical applications. While chitooligosaccharides were fairly soluble in aqueous solution and consequently facilitated their utilization in industrial application. Therefore, enzymatic production of chitooligosaccharides from chitosan, previously, was carried out using immobilized pepper chitosanase. Chitooligosaccharides I, II, III and IV groups were prepared with molecular weight> 100, 100-10, 10-1 and < 1 KDa, respectively. Their particles were compared with chitosan by scanning electron microscope (SEM). Their degree of fissure and cracking were increased with decrease the molecular weight. The rod shape appear in IV group, indicated to the presence of disaccharides (chitobioses). Ultraviolet spectrum (UV) showed that IV group had different absorbance at wavelength ranged from (309-348 nm) than that of the other groups. The main difference in Fourier transform infra red spectroscopy (FT-IR) of the four groups and native chitosan were observed in the range of the wave number 3750-3000 Cm-1. Potential antimicrobial activity (in vitro) of chitooligosaccharides groups were evaluated against some selected pathogenic microorganism and were compared with that of chitosan. They were measured using the standard method of diffusion disc plates on agar (50 µg/ml). Our results clearly indicated that the antimicrobial activities depend mainly on the type of microorganism tested. Chitooligosaccharides had antimicrobial activity as follows: groups (I, II, III) against B. cereus, group (I, III, IV) against B. subtilis, group (II, IV) against Staphylococcus aureus, group (II) against Pseudomonas aeruginosa, group (I, II, IV) against Candida albicans and group (III) against Saccharomyces chevalieri.
Keywords: Chitooligosaccharides, Scanning electron microscope (SEM), Ultraviolet (UV) spectrum, Fourier transform infra red spectroscopy (FT-IR), Pathogenic microorganism and Antimicrobial activity.